Shear Capacity on Corroded Fly Ash Reinforced Concrete Beam Using Galvanostatic Method - Merzy Mooy; Christiani Chandra Manubulu; Azarya Bees; Krisantos Ria Bela (Universitas Tribhuwana Tunggadewi Malang, 2024)
Corrosion can be triggered by a chemical reaction to the materials, establishing reinforced concrete's failure. For a long time, researchers have tried to find out how to prevent corrosion, a main structural construction issue. As a technology of waste material, fly ash has predominance, i.e., it is safer and greener than Portland cement. The finer size of fly ash can be an advantage in filling the concrete materials well. This research is about using fly ash as supplementary material on reinforced concrete beams and the galvanostatic method to accelerate corrosion. This research will compare the shear strength after corrosion of each normal beam and fly ash as a supplementary beam. A shear test of fly ash and a normal reinforced beam has been applied. Results showed that fly ash beams have 14% higher compressive strength and 3% higher shear strength with 14% smaller crack width than normal beams after corrosion. It also has a 3,5 times lower rate and 62% level of corrosion than normal beam